Outcomes for older telecare recipients: The importance of assessments. (March 2021) - Woolham, John; Steils, Nicole; Fisk, Malcolm; Porteus, Jeremy; Forsyth, Kirsty
Summary: This article explores the role of telecare assessment, review and staff training in meeting the needs of older people living at home. Using original empirical data obtained from an online survey of English local authorities it reveals considerable variation in assessment and review practice and in training given to social work and other staff who assess and review, which may impact on outcomes for telecare users. The study findings are situated within an English policy context and earlier findings from a large, government funded randomised controlled trial. This trial concluded that telecare did not lead to better outcomes for users. Findings: Our survey findings suggest that it may be the way in which telecare is used, rather than telecare itself that shapes outcomes for people who use it, and that 'sub-optimal' outcomes from telecare may be linked to how telecare is adopted, adapted and used; and that this is influenced by staff training, telecare availability and a failure to regard telecare as a complex intervention. Application: The findings may help to reconcile evidence which suggests that telecare does not deliver better outcomes and local authority responses to this which either discount or contest its value. The article suggests that to use telecare to achieve optimal outcomes for older people, social workers, care managers and other professionals involved in assessing for telecare will need to be given enhanced training opportunities, and their employers will need to perceive telecare as a complex intervention rather than simply a 'plug and play' solution.